State earned income tax credits and depression and alcohol misuse among women with children - Erin R. Morgan; Heather D. Hill; Stephen J. Mooney; Frederick P. Rivara; Ali Rowhani-Rahbar (Preventive Medicine Reports, 2022)
About 30% of single mothers in the US live at or below the poverty line. Poverty is associated with higher risk of depression and substance use. We investigated associations between state earned income tax credit (EITC) policies and reported depressive symptoms and alcohol misuse among birthing parents who responded to Pregnancy Risk Assessment Monitoring Survey spanning 1990–2017. Nearly half of birthing parents reported no more than a high school education (45.4%; 95% CI: 45.3%–45.6%). An estimated 28.5% of birthing parents reported binge drinking in the three months prior to conception (95% CI: 28.3–28.8%). Among birthing parents, each 10 percentage-point increase in the generosity of state EITC relative to the federal EITC was associated with a lower prevalence of binge drinking (prevalence ratio = 0.96; 95% CI: 0.93–0.99) prior to conception. This association was more pronounced among birthing parents with no more than high school education (prevalence ratio = 0.92; 95% CI: 0.88–0.97). There was no association between state EITC and number of reported depressive symptoms prior to conception or after birth, except among those with lower educational attainment (prevalence ratio = 0.94; 95% CI: 0.89–0.99). Anti-poverty policies such as EITC may reduce the burden of alcohol misuse, especially among people with children.